Species of Hybotinae from Podocarpus National Park, Ecuador (Diptera, Empidoidea, Hybotidae) - Rosaly Ale-Rocha (Revista Brasileira de Entomologia, 2016)
ABSTRACT The Hybotinae of the Podocarpus National Park were studied. Fourteen species are recorded and nine new species are described and illustrated: Euhybus pectinifemur sp. nov., Neohybos fuliginosus sp. nov., Neohybos globosus sp. nov., Neohybos rostratus sp. nov., Neohybos serratus sp. nov., Neohybos spinosus sp. nov., Syndyas longiventris sp. nov., Syneches flavithorax sp. nov. and Syneches polleti sp. nov. A key to Neohybos species from Ecuador is also presented.